PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION BERBANTUAN MEDIA KARTU CAPIT TERHADAP KEMAMPUAN NUMERASI SISWA KELAS V - Suryaningsih, Tri; Ana Nursyifa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the Realistic Mathematics Education (RME) approach assisted by claw card media on students’ numeracy skills in learning the volume of three-dimensional figures at MI Nurul Islam. The research employed a quasi-experimental method with a posttest-only control group design. The sampling technique used was purposive sampling involving two classes, namely an experimental class consisting of 24 students taught using the RME approach assisted by claw card media and a control class consisting of 24 students taught using the jigsaw-type cooperative learning approach. Data were collected using an essay test comprising ten questions to measure students’ numeracy skills. The data were analyzed using an Independent Samples t-test. The results showed a significance value of 0.000 < 0.05, indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. These findings indicate that the RME approach assisted by claw card media has a significant positive effect on students’ numeracy skills in learning the volume of three-dimensional figures. The study implies that the integration of contextual learning approaches with concrete instructional media can enhance students’ conceptual understanding and numeracy skills in mathematics learning